Rule of law in the EU - Peršak, Nina (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2019)
The article examines the existing rule of law efforts and rule of law challenges in the EU, specifically those linked to the functioning of justice systems and EU criminal law. First, the legal framework of the principle of the rule of law is presented, then the measures for its realisation in practice, and finally the different understanding of the role of the principle in the context of criminal law. The principle is pursued in a dialogue between the Commission and the Member States and at the same time at the EU level. The Treaty on the Functioning of the European Union explicitly defined competences in the field of criminal law. Therefore, the principle of the rule of law can be regarded at the EU level also as a tool for limiting the criminal-law lawmaking activity of the EU bodies. The article analyses the fundamental judgments of the EU Court that demonstrate the scope of the restrictive role of the principle of the rule of law. EU criminal law can function as a means of strengthening and a means of undermining the rule of law. Strengthening of criminal jurisdiction has also brought about the creation of mechanisms that strengthen the democratic legitimacy of EU legislation, in particular by strengthening the role of the European Parliament. On the other hand, criminal law jurisdiction remains firmly linked to EU objectives and policies, and EU criminal law can still be understood primarily as a tool for achieving EU policy goals. The article identifies various aspects of the rule of law in the context of EU criminal law and concludes by revealing some outstanding rule-of-law challenges yet to be fully addressed in the EU.
Keywords: criminal law policy; EU criminal law; kazensko pravo EU; kazenskopravna politika; mutual trust; načelo (kazenskopravne) škode; načelo vladavine prava; Okvir EU za krepitev načela pravne države; Pogodba o delovanju Evropske unije; rule of law; Rule of Law Framework; the harm principle; Treaty on the Functioning of the EU; vzajemno zaupanje